Imunização de camundongos BALB/C com as proteínas recombinantes TSA, LelF e STI de Leishmania (Viannia) braziliensis e avaliação da eficácia da vacina - Matos, Grazzielle Guiamrães de (2016)
In Brazil, L. (V.) braziliensis is specie responsible for many cases of American Tegumentary Leishmaniasis (ETL). To effective vaccine development, formulations contained immunogenic antigens associated with adjuvants that induce a T helpe 1 (Th1) immune response are been investigated, among of antigen have the “Thiol Specific Antioxidant” (rTSA), “Stress Inducible protein 1” (rSTI) and “Leishmania elongation initiation fator” (rLeIF) of L. major, which have been immunogenic and promising. The genes that corresponding to these antigens in L. (V.) braziliensis were sequenced and recombinants proteins were obtained and used in this study. Works that used BCG and β-glucan showed that these could provide protection against not related pathogens. The present study had as aim to evaluate the immunogenicity and the effectiveness of the vaccine using the rTSA, rSTI and rLeIF proteins (Triple), associated or not with β-glucan, with or without BCG stimulus. BALB/c mice were divided in 2 groups, one of the groups was stimulated with BCG and the other not. Posteriorly, the animals were divided in subgroups and vaccinated with triple, associated or not with β-glucan. Mice’s serum were collected to search of cytokines and antibodies by immunoenzymatic technique. Lymph node and spleen’s cells were cultivated and cytokines searched in supernatants. BCG stimulation induced a greater IFN-γ production. The vaccinated mice with triple produced IgG total, IgG1 and IgG2a specifics to L. (V.) braziliensis. BCG stimulation induced a high IgG total and IgG2a production in animals that received the triple without β-glucan. To evaluate the protection provided by vaccine, the immunized animals were infected with L. (V.) braziliensis and paw them measured along of 8 weeks. The subgroup don’t stimulated with BCG and vaccinated with triple, associated with β-glucan, has developed bigger lesions that the others subgroups. The subgroups that received only BCG stimulation or BCG stimulation and vaccine with triple plus β-glucan presented bigger lesions that animal don’t stimulated or vaccinated. After infection by L. (V.) braziliensis, (i) the animals stimulated with BCG and vaccinated with triple presents more IgG specific to L. (V.) braziliensis; (ii) the immunizations with triple maintained IFN-γ levels elevated; (iii) all animals presented lower IL-17 levels in serum; (iv) the subgroups produced similar IFN-γ levels, but with a high IL-17 production in subgroup vaccinated with triple plus β-glucan, don’t BCG stimulated, in spleen; (v) the animals that received only BCG produced more IFN-γ and IL-17 in lymph node. In conclusion: the immunizations with triple were immunogenic; the immunization scheme containing triple plus β- glucan, without BCG stimulation, provided partial protection against L. (V.) braziliensis infection; BCG stimulations induced biggest lesions in subgroup that received only saline or triple plus β-glucan; the vaccination scheme containing triple maintained high IFN-γ production after L. (V.) braziliensis infection; in infection site, the BCG stimulation induced a Th1/Th17 heterologous response.